Imbalance between interleukin-6 and adrenomedullin mRNA levels in peripheral blood mononuclear cells of patients with lupus nephritis - Nishitani, Y (Blackwell Science Inc, 2001)
In this study, we measured the mRNA levels of adrenomedullin (AM), C-type natriuretic peptide, vascular endothelial growth factor, interleukin-1β (IL-1β) and interleukin-6 (IL-6) in peripheral blood mononuclear cells (PBMC) of 34 patients with lupus nephritis (LN) (15 active and 19 inactive) and 30 healthy volunteers. mRNA levels were measured using a real-time quantitative PCR method. Compared with healthy volunteers, IL-6 mRNA levels were elevated in LN patients (P < 0·005), while AM mRNA levels were decreased (P < 0·05). Also, IL-6 mRNA levels were higher and AM mRNA levels lower in active LN patients compared with inactive LN patients. In addition, IL-6 mRNA levels positively correlated and AM mRNA levels negatively correlated with SLE disease activity index and laboratory findings, such as blood urea nitrogen, serum creatinine, 50% haemolytic unit of complement and urinary excretion of protein over 24 h. Furthermore, IL-6 mRNA levels were negatively correlated with AM mRNA levels within the same LN patients. With regard to pathological findings, our results showed that IL-6 mRNA levels were higher, and AM mRNA levels significantly lower in patients with a high activity index compared to those with a low activity index. Following treatment with prednisolone, IL-6 mRNA levels in active LN patients decreased and AM mRNA levels increased to levels comparable to those in inactive LN and healthy volunteers. In vitro studies further demonstrated that elevated IL-6 mRNA levels in active LN patient PBMC were suppressed by the addition of adrenomedullin. Our results suggest that an imbalance between IL-6 and AM levels may play an important role in the progression of SLE, and that the mRNA levels of these genes in PBMC may be used as a disease activity index for SLE.